(untitled) (International Seven Journal of Health Research, 2023)
The Morphofunctional discipline combined with Integrated Practices within the Medicine course involves modalities composed of anatomy, cell biology, physiology, histology, histopathology, laboratory practices, addressing the main morphological, anatomical and functional aspects of cells, tissues, organs and systems of the body human.The Human Anatomy Monitoring Project plays an extremely important role in consolidating knowledge and developing greater interest in the area among monitored students, by allowing greater contact with practical environments, as well as with the experience of students in more advanced periods of the course. course. Monitoring activities take place in the morphofunctional and Integrated Projects (PI) laboratory, which has a large collection of synthetic parts that bear a great resemblance to cadavers, projectors, microscopes, incubators and storage locations for biological elements. Therefore, the present study corresponds to an experience report on the activities carried out by monitoring within the Morphofunctional and Integrated Practices discipline. The objective of the work is to report how the monitoring modality works at a Private University in the interior of the State of São Paulo, exposing the mutual contributions that such activity makes, both for students entering the course and for the monitors. In this way, the activities carried out during this helped the participating students to become more interested in the content of the discipline, understand the importance of anatomy and other areas for a medical career, in addition to developing a human, critical and reflective professional, with general skills established in health, decision making, communication and leadership.